CULTIVATION AND MOLECULAR CHARACTERISATION OF Auricularia SPECIES IN SOUTHWESTERN NIGERIA (2017)
Mushrooms such as Pleurotus, Vovariella and Auricularia species are cultivated for food and medicinal purposes in the world. However, cultivation of Auricularia in Nigeria is limited due to inadequate information on its characteristics, nutritional contents and cultivation requirements. Hence, this study was designed to characterise Auricularia species in Southwestern Nigeria and determine suitable substrates for their cultivation. Fifty-four samples of Auricularia species were randomly collected based on availability from secondary forests in Osun (11), Oyo (10), Ondo (9), Ekiti (8), Ogun (8) and Lagos States (8). Pieces of tissue from each sample were cultured on Potato Dextrose Agar (PDA). Samples with mycelial growth were later cultured on sterilised sorghum grains to produce spawns. Six substrates comprising Mansonia altissima. (A. Chev) A. Chev sawdust, cotton waste Gossypium hirsutum Linn, rice straw Oryza sativa Linn, each in polyethylene bags and drilled logs of Mangifera indica Linn, Gliricidia sepium (Jacq) Walp, and Cedrela odorata Linn, were purposively selected for spawn inoculation to produce mushrooms. Morphological identification (colour, shape and texture) of Auricularia species, the growth parameters (days of spawn run, days of pin head formation), and yield of the mushrooms were determined using standard procedures. Nutrient (nitrogen, phosphorus, and potassium) and proximate analysis (Protein, Fat, and Carbohydrate) were carried out using AOAC methods. Fifteen Random Amplified Polymorphic DNA (RAPD) primers were used for PCR amplification of the DNA of Auricularia samples, to determine the degree of genetic diversity. Phylogenetic relations were determined by cluster analysis, Polymorphic Information Content (PIC) and genetic diversity determined using standard procedures. Data were analysed using descriptive statistics, clustering and Principal Component Analyses (PCA). UNIVERSITY OF IBADAN LIBRARY iii Morphologically, 31 samples of A. auricula, (yellow brown, auriform, leathery texture) and 12 samples of A. polytricha (dark brown, discoid, gelatinous) were identified, while 5 samples were unidentified and 6 samples did not grow. Auricularia species samples cultivated on M. altissima sawdust, cotton waste, rice straw in bags produced mycelial growth, but did not fructify while samples on drilled logs had mycelial growth and fructified. Mangifera indica had highest days of spawn run (24.3±0.7), pin head formation (28.7± 0.6) and highest yield (10.0±0.4 g). The highest nitrogen content (13.6 ±0.7 mg/kg) was recorded in A. polythrica, phosphorus (39.3±7.6 mg/kg) in A. auricula and calcium (61.9 ± 3.6 mg/kg) in A. auricula. The highest protein (7.0±0.8%) and crude fibre (25.1±2.5%) were obtained in A. polythrica. Fat content (7.0 ± 0.1mg/kg) was highest in A. auricula. Cluster analysis and morphological traits produced 6 distinct groups while the PCA produced eigenvalues of 23.0 %, 16.0 %, 14.0 %, 11.0 %, 10.0 % and 9.0 % on six corresponding axes. The RAPD primers grouped the Auricularia species into 6 distinct clusters based on morphological traits. The PIC ranged from 0.5594 (OPH-15) to 0.7819 (OPB-12) and gene diversity from 0.5930 (OPH-15) to 0.7977 (OPB-12). Primer OPB-12 was the most informative for genetic diversity of Auricularia species. Auricularia species exhibited genetic variations and Mangifera indica enhanced their growth. Auricularia polytricha was the most nutritious species recorded. Keywords: Mushroom cultivation, Mangifera indica substrate, Polymorphic information content. Word Count: 495